PENERAPAN MONITORING JARINGAN DENGAN ZABBIX PADA PT. PLN (PERSERO) UIP BAGIAN SUMBAGSEL - Ariyadi, Tamsir; Fikri, Muhammad; Irwansyah, Irwansyah; Yudiastuti, Helda (LPPM Universitas Putera Batam, 2024)
PT PLN (Persero) UIP SUMBAGSEL, as a government company in the energy sector, faces challenges in ensuring reliable and efficient internet network access for employees. The lack of a monitoring system that assists administrators in monitoring network devices causes difficulties in ensuring consistent device status and connectivity. Zabbix is an open-source software for network monitoring, offering an effective solution to monitor network performance and detect problems in real-time. This research aims to design and implement a network monitoring system using Zabbix at PT PLN (Persero) UIP SUMBAGSEL. The research method used is Network Development Life Cycle (NDLC), which includes the stages of analysis, design, simulation, implementation, monitoring, and management. The results showed that Zabbix is able to detect Mikrotik devices connected to the network and monitor device performance, such as network traffic and memory usage. In conclusion, the implementation of monitoring with Zabbix is effective for monitoring the availability of network devices, which is expected to increase operational efficiency and productivity at PT PLN (Persero) UIP SUMBAGSEL.